Comparison of Detection Rate of Root Canal Orifices of Maxillary First Molar Using Various Techniques: An in-vivo Study - Amit Kumar Garg; Neha Agrawal; Kulwinder Kaur Wadhwani; Aseem Prakash Tikku (Association of Support to Oral Health Research (APESB), 2021)
Objective: To compare the detection rate of root canal orifices of maxillary first molar by various techniques in the Indian population. Material and Methods: A total of 50 maxillary 1st molar cases were selected and sequentially divided into four groups: Group I: Naked eye; Group II: Surgical loupe; Group III: Surgical operating microscope; and Group IV: Fluorescein sodium dye. After access opening, the number of root canal orifices was detected in all cases with these methods. Results: By naked eye and surgical loupe, a total of 171 root canal orifices were detected, by a surgical operating microscope, 176, and by fluorescein sodium dye, 177 root canal orifices were detected. The detection rate of root canal orifices is as follows: Group I (96.61%) = Group II (96.61%) < Group III (99.44%) < Group IV (100%) and detection rate of MB-2 canal orifices Group I (40%) = Group II (40%) < Group III (50%) < Group IV (52%). No significant difference in the number of canal orifices detected could be seen for any of the comparisons. No significant difference was observed between the naked eye and surgical loupe techniques. Although the surgical operating microscope detected more root canal orifices, it did not have a significantly higher detection than the other two techniques. Conclusion: No significant difference was seen among various methods. However, the use of a surgical operating microscope and fluorescein sodium dye increased the detection rate of root canal orifices.